Mutual Coupling Reduction in Antenna Using EBG on Double Substrate - Raimi Dewan; M. K.A. Rahim; M. R. Hamid; M. E. Jalil; H. A. Majid (Universitas Ahmad Dahlan, 2017)
In this paper, a mutual coupling studies is conducted between two-element array antenna on dual substrate. A single patch antenna is firstly designed on dual substrate layer to testify appropriate performance at 2.45 GHz. Subsequently, an array of two element patches on dual substrate are constructed with one of them is incorporated with three EBG unit cell on the bottom substrate. The radiating patch is on the top substrate, while the EBG unit cells is on the bottom substrate. With EBGs in separate layers from the antenna array, the antenna elements are closely separated by a distance of 22 mm with a significant reduced mutual coupling of -26.61 dB. This correspond to a distance reduction of 34.68%. The proposed structure implemented only three EBG unit cells. Apart from that, the study of overlapped case of EBG with the antenna is also presented.